Characterization and analysis of landslides of April 5, 2012 Chosica-Lima - Guadalupe Gómez, Enrique (2012)
Flows of mud and mud known as the Peruvian coast landslides are recurring geological phenomena, especially in the area of ​​Chosica. The formation of the avalanche starts with the physical, chemical and biological weathering, next to fracturing and faulting of rocks of the Batholith Andino, where for long periods rocks deteriorate exfoliating, disintegrating, also forming rocks spheroidal disjunction, ie, large diameter rocks subrounded to subangulosas, reaching sizes of sand and clay. Subsequently, from this, for erosion and transport due to intense and short rains in the basin, make mud flows called landslides that descend impetuously both major streams, secondary and side gullies to form the mainstem, and such as competence and geodynamic behavior, either by erosion or deposition (burial) destroy the various buildings and services for the people. Finally, characterized and analyzed most of the landslides occurred on the left bank of the Rimac river, formed by the streams Cantuta, Santo Domingo, Mariscal Castilla, La Ronda, California and landslides occurred on the right bank, formed by the streams Quirio, Pedregal Freedom Carossio and Corrales.